Design of A Dual-Band Microstrip Antenna for 5G Communication - Ahmad Firdausi; Lusi Damayanti; Galang Persada Nur Hakim; Umaisaroh Umaisaroh; Mudrik Alaydrus (Journal of Integrated and Advanced Engineering (JIAE), 2021)
The necessity for mobile communication devices is increased rapidly. Users expect to get very fast information access and data access without delay. The fifth-generation (5G) development in wireless mobile telecommunication technology promises capacity enhancement, ease connectivity, high efficiency, and high data rate transmission. The appropriate device should support this improvement of the technology. The antenna is one of the main devices to support the high data rate transmission. This paper proposed designing a dual-band rectangular patch antenna in 29 GHz and 38 GHz that supports 5G technology. This microstrip antenna is composed of 4 patch array elements to obtain higher gain. The material used for this microstrip antenna is RT Duroid 5880 with a dielectric constant of 2.2 and a thickness of 1.575 mm. Both measurement and simulation are confirmed that the 2×2 array microstrip antenna in 29 GHz and 38 GHz frequency have a return loss value of -12.5 dB and -16 dB, respectively. The bandwidth for both frequencies has a value of 4.5 GHz and 3.75 GHz.